Analysis of aceclofenac and bovine serum albumin interaction using fluorescence quenching method for predictive, preventive, and personalized medicine. Issue 1 (December 2015) - Koly, Sabiha; Kundu, Sangita; Kabir, Shaila; Amran, Mohammad; Sultan, Md.
Abstract Background The study of the interaction of a drug with plasma protein is very important because drug-protein binding plays an important role in determination of pharmacological and toxicological properties of drugs. Our study was designed to investigate the interaction between aceclofenac and bovine serum albumin (BSA) using fluorescence spectroscopy at different temperatures (298 and 308 K). Methods Fluorescence spectroscopy was used to carry out the study. Fluorescence quenching constant was determined from Stern-Volmer equation. Van't Hoff equation was used to determine the thermodynamic parameters such as free energy (ΔG ), enthalpy (ΔH ), and entropy (ΔS ). Results The experimental data showed that the quenching of BSA by aceclofenac was due to a formation of a BSA-aceclofenac complex with probable involvement of both tryptophan and tyrosine residues of BSA. Dynamic quenching was shown for BSA by aceclofenac at the experimental conditions. The values of thermodynamic parameters indicated that the hydrophobic forces played major roles for BSA-aceclofenac complexation. The binding number (n ) was found to be ≈1 indicating that 1 mol of BSA bound with 1 mol of aceclofenac. The binding affinity of aceclofenac to BSA was calculated at different temperatures. It was shown that the binding constant decreased with increasing temperatures indicating that stability of the BSA-aceclofenac complex decreased with increasing temperatures. Conclusions The interaction of aceclofenac with BSA was successfully explored using a fluorescence spectroscopic technique.